The effectiveness of employing the memory game strategy in teaching primary school students in Arabic grammar (Journal of the College of Basic Education, 2022)
This research aims to know the effect of the memory game strategy in teaching primary school students in Arabic grammar by verifying the validity of the following null hypothesis: (there is no statistically significant difference between the mean scores of the experimental group and the mean scores of the control group in the achievement test The researcher adopted the experimental design as being the most appropriate for the research groups, as it included the experimental and control groups on the post test. for the experimental group and (31) male and female students for the control group, and the experimental group taught by the memory game strategy outperformed the control group that taught by the traditional method